Hypolipidemic Potential of Roselle Calyces (Hibiscus sabdariffa) Extracts and Passion Fruit (Passiflora edulis) Juice with Pulp Concentrate Formulations in High Fat Diet-Fed Rats - Janthakhin, Yoottana; Tunsophon, Sakara; Donrung, Nowwapan; Sutthiwong, Nuthathai; Khongrum, Jurairat; Gussayakorn, Boonruksa; Kaewkaen, Pratchaya; Chonpathompikunlert, Pennapa (Trends in Sciences, 2024)
Obesity contributes to cardiometabolic risk factors, including type 2 diabetes mellitus, hypertension, and dyslipidemia. In this study, we aimed to investigate the hypolipidemic potential of various formulations of Roselle Calyces (Hibiscus sabdariffa) extracts and Passion Fruit (Passiflora edulis) juice with pulp concentrate on high-fat diet (HFD) induced obese rats. Male Sprague Dawley rats were divided into seven groups: (1) control group, (2) HFD group, (3) HFD treated with passion fruit juice with pulp concentrate group, (4) HFD treated with roselle calyces extract group, (5) HFD treated with mix roselle calyces extract plus passion fruit juice with pulp concentrate in powdered form group, (6) HFD treated with a jelly drink containing polyphenol-rich roselle calyces extract and passion fruit juice with pulp concentrate group, and (7) HFD treated with simvastatin group. The results revealed that HFD-fed rats exhibited an increase in body weight, atherogenic and adiposity indices, serum triglyceride (TG), total cholesterol (TC), low-density lipoproteins (LDL), and decreased high-density lipoproteins (HDL) levels compared to control rats. Interestingly, all of these formulas namely the roselle calyces extract, the passion fruit juice with pulp concentrate, the combination of roselle calyces extract plus passion fruit juice with pulp concentrate (RP powder), and the jelly drink containing polyphenol-rich roselle calyces extract and passion fruit juice with pulp concentrate could normalize lipid profiles levels including TG, TC, LDL and increased HDL in HFD-fed rats. Our findings provide significant information for the commercial development of functional ingredients or foods with hypolipidemic properties. HIGHLIGHTS High-fat diet (HFD) fed-rats presented increases in body weight, atherogenic and adiposity indices compared to control diet (CD) fed-rats. HFD fed-rats exhibited increasing serum triglyceride (TG), total cholesterol (TC), low-density lipoproteins (LDL), and decreasing high-density lipoproteins (HDL) levels compared to CD fed-rats. Formulations of Roselle Calyces (Hibiscus sabdariffa) extracts and Passion Fruit (Passiflora edulis) juice with pulp concentrate alleviated metabolic alterations in HFD fed-rats. GRAPHICAL ABSTRACT